Recurrent Massive Hydrothorax in a Patient with Decompensated Liver Cirrhosis - K. S. Zemlyanukhina; I. N. Tikhonov; M. S. Zharkova; O. Yu. Kiseleva; R. Т. Rzayev; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to demonstrate the need for a detailed differential diagnosis and selection of therapy in a patient with decompensated liver cirrhosis of combined etiology (HCV infection and primary sclerosing cholangitis).   Key points. The patient came to the clinic with complaints of shortness of breath with minimal physical activity, abdominal enlargement, swelling of the legs, yellowness of the skin, and severe weakness. The complaints arose two months after suffering from left-sided focal pneumonia. Laboratory tests revealed signs of systemic inflammation, liver failure, and acute kidney injury. According to the results of instrumental studies, massive hydrothorax was noted in the right pleural cavity. The patient underwent a series of thoracentesis, and a total of about four liters of non-inflammatory pleural fluid was evacuated. Differential diagnosis was based on the presence of dyspnea and respiratory failure. The patient received effective antiviral therapy with drugs using an interferon-free regimen. Subsequently, conservative therapy was carried out, against the background of which the symptoms regressed and the patient’s condition improved.   Conclusions. Hepatopleural syndrome is a serious complication in patients with decompensated liver cirrhosis, although it does not always appear secondary to massive ascites. To resolve hepatic hydrothorax, it is necessary to carry out diuretic therapy, replacement transfusion therapy with albumin preparations, and if there is a large amount of fluid in the pleural cavities, therapeutic and diagnostic thoracentesis is recommended.